Direct Synthesis of Palladium Catalyst on Supporting WS2 Nanotubes and its Reactivity in Cross‐Coupling Reactions. Issue 10 (12th June 2015) - Višić, Bojana; Cohen, Hagai; Popovitz‐Biro, Ronit; Tenne, Reshef; Sokolov, Viacheslav I.; Abramova, Natalya V.; Buyanovskaya, Anastasiya G.; Dzvonkovskii, Sergei L.; Lependina, Olga L.
Abstract Palladium nanoparticles were deposited on multiwall WS2 nanotubes. The composite nanoparticles were characterized by a variety of techniques. The Pd nanoparticles were deposited uniformly on the surface of WS2 nanotubes. An epitaxial relationship between the (111) plane of Pd and the (013) plane of WS2 was mostly observed. The composite nanoparticles were found to perform efficiently as catalysts for cross‐coupling (Heck and Suzuki) reactions. The role of the nanotubes′ support in the catalytic process is briefly discussed.